Liquid-phase exfoliated graphene: functionalization, characterization, and applications - Quintana, Mildred; Tapia, Jesús Iván; Prato, Maurizio (Beilstein Journal of Nanotechnology, 2014)
The development of chemical strategies to render graphene viable for incorporation into devices is a great challenge. A promising approach is the production of stable graphene dispersions from the exfoliation of graphite in water and organic solvents. The challenges involve the production of a large quantity of graphene sheets with tailored distribution in thickness, size, and shape. In this review, we present some of the recent efforts towards the controlled production of graphene in dispersions. We also describe some of the chemical protocols that have provided insight into the vast organic chemistry of the single atomic plane of graphite. Controlled chemical reactions applied to graphene are expected to significantly improve the design of hierarchical, functional platforms, driving the inclusion of graphene into advanced functional materials forward.
Keywords: applications; dispersions; graphene; organic functionalization; ultrasonication